Application of rare earth elements as modifiers for Ni-rich cathode materials for Li-ion batteries: a mini review - Zybert, Magdalena; Ronduda, Hubert; Raróg-Pilecka, Wioletta; Wieczorek, Władysław (Frontiers in Energy Research, 2023)
This mini review article summarizes the recent progress in the modification of Ni-rich cathode materials for Li-ion batteries using rare earth elements. Although layered materials with high nickel content are the most promising cathodes due to their high capacity, the significant chemical, structural and thermal instability considerably hinders their practical application. Overcoming these limitations is possible through morphological or structural modifications based on doping and coating. Numerous reports regarding the use of various elements of the periodic table for this type of modification can be found in the literature. Surprisingly, rare earth elements are the least applied and described in the literature so far, even though they possess all the necessary features qualifying them as effective modifiers of layered cathode materials. This work summarizes the up-to-date publications regarding the application of rare earth elements as a highly prospective group of modifiers for layered Ni-rich cathode materials. These reports provide a better understanding of mechanisms of modification by rare earth elements and their beneficial effects on the electrochemical performance of the studied materials. New prospective strategies for layered cathode materials improvement have also been indicated.